(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In the article, aloe medicinal plant seedlings were grown in outdoor and greenhouse conditions on special substrates made of a mixture of soil+sand+rotted cattle manure for 4 years using rain and drip irrigation methods. It was found that the total amount of water used during the year was 1400 m3/ha in the drip irrigation method, and 2569 m3/ha in the sprinkler irrigation method